Polluted earth : the science of the earth's environment - Gates, Alexander E., 1957-; John Wiley & Sons (Hoboken, New Jersey : Wiley, 2023)
"With sustainability having become a key issue for all scientific disciplines, earth science departments have been redesigning their courses to focus more and more on environmental aspects. Current environmental geology textbooks are primarily retooled general geology or physical geology textbooks with some true environmental geology topics added but not integrated into the main chapters of the books. Since most introductory geology courses are attended by non-science majors who are unfamiliar with science textbooks and not easily engaged by them, these textbooks are not effective in engaging or educating the majority of the students in the class. Textbooks can be much more engaging and instructive if the approach is changed, e. g. by discussing case studies instead of a theoretical framework"--
Humans and the Environment -- Environmental Justice -- Architecture of the Earth and Atmosphere -- Climate Change: Crisis of our Time -- Natural Pollution -- Environmental Perspective on Rocks and Minerals -- Natural Hazards and Pollution -- Pollution of Groundwater -- Pollution of Rivers and Surface Waters -- Pollution of Soil -- Ecosystem Pollution -- Ocean Pollution -- Weather and Air Pollution -- Mining and Earth Resources -- Military and Pollution -- Agricultural Pollution -- Nuclear Energy and Dangers -- Solid Waste Disposal -- Environmental Industry and Cleanup -- Is It Too Late?
Includes bibliographical references and index.
Keywords: Environmental degradation; Nature -- Effect of human beings on; Environmental protection; Earth (Planet) -- Pollution